Studying the Optimal Conditions for the Biodegradation Process of Plastic Materials by Pseudomonas Aeruginosa - Mohammed Hasan, Rawaa (Kerbala Journal of Nursing and Health Sciences., 2025)
Monoester is produced as a consequence of the ester bond hydrolysis mechanism used by microorganisms to degrade Polyhydroxyalkanoates (PHAs). Following its breakdown, this monoester yields alcohol and phthalic acid (PA). The current work was aimed to study the ability of P. aergiounas to degradation of hydrocarbons after determining the optimal conditions for the process. A sample of plastic water bottles was obtained from local marketplaces in Babylon city. Swabs were collected from the rumen of cows, sheep, and goats and immediately sent to the laboratory for culture. The swabs were placed on blood agar and subjected to incubation at a temperature of 37°C for a duration of 24 hours. Pseudomonas aeruginosa isolates were classified based on their morphological and biochemical features. The present investigation revealed the optimal conditions for bacterial growth and cell proliferation. The current study demonstrates variations in cell counts at different pH levels (5, 6, 7, and 8) and temperatures (23, 30, 37, and 44) under varying plastic concentrations. The optimal circumstances for P. aeruginosa were a pH of 7, a concentration of 1ml, and a temperature of 37°C. The results demonstrate the capacity of bacteria to degrade by quantifying the viable bacterial population that grows on MSM. The viable count of Pseudomonas first grew on the first day and subsequently declined during the course of the experiment. The percentage of biodegradation for P. aeruginosa was 59.31. It is concluded from the current study that P. aeruginosa isolated from the rumen of some ruminants (cows, sheep and goats) has the ability to biodegradation of plastic materials.